PENGARUH METODE SNOWBALL THROWINGTERHADAP PERUBAHAN PERILAKU MENGGOSOK GIGI - Eppy Setiyowati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Tooth decay is experienced by many children, such as cavities, tartar, inflammation of  the gums, sensitive teeth, and bad breath, the cause is an mistake when brushing of teeth . The snowball throwing learning method is cooperative towards changes in brushing behavior, because the learning model is effective in training students to brush their teeth, the aim of the researchers was to analyze the effect of the snowball throwing method on changes in brushing behavior in 4th grade children at SDN Jagir 1/393 Surabaya.The research method is Pre-Experimental with approach to One group pre-post tes design, the number of samples is 65 students from grade 4 at SDN Jagir 1/393 Surabaya. The technical sampling uses simple random sampling, data collection uses a questionnaire, then the data is processed and analyzed using paired T-test (α = 0.05). The results showed that after a paired T-test statistical test, the value of = 0.000 and α = 0.05 means that < α, H0 is rejected, meaning there is an influence of the snowball throwing method on changes in brushing behavior of school children at SDN Jagir 1/393 Surabaya.Conclusion of the study, the snowball throwing method provides an increase in the behavior of brushing teeth, that the students practice brushing their teeth twice in the morning and night before going to bed properly. Suggestion, the snowball throwing method can be applied in schools for learning activities.